Price Monitoring Automation with Marketing Forecasting Methods - Penkova, Oksana; Zakharchuk, Oleksandr; Blahun, Ivan; Berger, Alina; Nechytailo, Veronika; Kharenko, Andrii (My University, 2022)
The main aim of the article is to solve the problem of automating price monitoring using marketing forecasting methods and Excel functionality under martial law. The study used the method of algorithms, trend analysis, correlation and regression analysis, ANOVA, extrapolation, index method, etc. The importance of monitoring consumer price developments in market pricing at the macro and micro levels is proved. The introduction of a Dummy variable to account for the influence of martial law in market pricing is proposed, both in linear multiple regression modelling and in forecasting the components of the Consumer Price Index. Experimentally, the high reliability of forecasting based on a five-factor linear regression model with a Dummy variable was proved in comparison with a linear trend equation and a four factor linear regression model. Pessimistic, realistic and optimistic scenarios were developed for forecasting the Consumer Price Index for the situation of the end of the Russian Ukrainian war until the end of 2023 and separately until the end of 2024. Keyword Основною метою статті є вирішення проблеми автоматизації моніторинг цін за допомогою методів маркетингового прогнозування та Excel працездатність в умовах воєнного стану. У дослідженні використовувався метод алгоритми, аналіз тенденцій, кореляційний і регресійний аналіз, ANOVA, екстраполяція, індексний метод тощо. Важливість моніторингу споживчих цін у ринковому ціноутворенні на макро- і мікрорівні доведено. Введення манекена змінна для врахування впливу воєнного стану на ринку пропонується ціноутворення як у моделюванні лінійної множинної регресії а також у прогнозуванні складових індексу споживчих цін. Експериментально доведена висока достовірність прогнозу на основі а п'ятифакторна модель лінійної регресії з фіктивною змінною доведено у порівнянні з лінійним рівнянням тренду та чотирифакторною моделлю лінійної регресії. Песимістичний, реалістичний і були розроблені оптимістичні сценарії прогнозування Індекс споживчих цін для ситуації закінчення російсько-української війни до кінця 2023 року та окремо до кінця 2024 року.
Keywords: кафедра маркетингу; Excel; consumer price index; pricing; linear multivariate regression; forecast; індекс споживчих цін; ціноутворення; лінійна багатовимірна регресія; прогноз